2002
DOI: 10.1159/000049035
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Significance of Chronic Hepatitis-Related Viruses Infection in Hemodialysis Patients from Taiwan

Abstract: Background/Aims: A novel DNA virus which was designated TT virus (TTV) in 1997 was considered a possible hepatitis-related virus, like hepatitis C (HCV), hepatitis B (HBV) and GB virus C/hepatitis G viruses (GBV-C/HGV). In the present study, the molecular epidemiology and clinical significance of TTV, GBV-C/HGV and HCV infection in hemodialysis patients from Taiwan are investigated. Methods: Sera of 85 patients on maintenance hemodialysis were tested for alanine aminotransferase (ALT), hepatitis B surface anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…However, the GBV-C/HGV or TTV infection was not associated with elevated serum ALT levels. 6,7 The most critical affect on elevated serum ALT levels in uremic patients was from HCV infection. The clinical implication and etiological importance of an association between liver diseases and SENV infection still remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the GBV-C/HGV or TTV infection was not associated with elevated serum ALT levels. 6,7 The most critical affect on elevated serum ALT levels in uremic patients was from HCV infection. The clinical implication and etiological importance of an association between liver diseases and SENV infection still remain uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Other parenterally transmitted viruses which have been suggested as candidates for hepatitis of unknown origin include GB virus C/hepatitis G virus (GBV-C/HGV) 4 and TT virus (TTV), 5 which are also epidemic among uremic patients. 6,7 However, our previous studies have failed to show an association between liver disease and either GBV-C/HGV or TTV infection in uremic patients. 6,7 A new family of DNA viruses was recently isolated and designated as SEN virus (SENV).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[3,4] Many studies have reported the prevalence of TTV infection in hemodialysis patients. [5][6][7][8][9] Patients on hemodialysis are at risk of parenteral infections, including viral hepatitis. Patients on peritoneal dialysis are also prone to infections via contamination during exchange of peritoneal dialysate.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most common viral infections are caused by hepatotropic or other hepatitis-associated viruses such as hepatitis B virus (HBV) [8] , hepatitis C virus (HCV) [9] , HGV [10] and transfusion-transmitted virus [11] . In recent years, a high prevalence of HGV infection among end-stage renal disease and chronic HD patients has been well documented, varying between 6 and 44%, in different countries [12][13][14][15] . Analysis of the 5 untranslated region (UTR) has led to the suggestion that variants of HGV can be divided into fi ve genotypes [16] .…”
mentioning
confidence: 99%